Historia historii syberyjskiego związku Anny Slepcowej i Wacława Sieroszewskiego - Kopeć, Zbigniew (Białostockie Studia Literaturoznawcze, 2021)
The paper discusses the means of presentation within the field of Polish studies of the relationship between Wacław Sieroszewski, a writer and ethnographer, one of the better known Polish exiles in Siberia, and a Yakut woman, Anna Sleptsova. The author contemplates why in the Polish studies their relationship has been omitted, marginalized or hyperbolized. This resulted from Sieroszewski’s own reticence and the cultural taboo, which prohibited exiles from entering into relationships with Russian women. Additionally, the paper presents some Russian-language studies concerning Sieroszewski, in which Sleptsova, who was a significant writer and researcher for Yakutia, is openly referred to as Sieroszewski’s wife. kzbsz@amu.edu.pl Instytut Filologii Polskiej, Uniwersytet im. Adama Mickiewicza w Poznaniu Brzozowski Stanisław (1983), Płomienie. Z papierów po Michale Kaniowskim, Warszawa: Iskry. Chrostek Mariusz (2008), Etos dziewiętnastowiecznych zesłańców, Wrocław: Polskie Towarzystwo Ludoznawcze. Cixous Hélène (1993), Śmiech Meduzy, przeł. A. Nasiłowska, „Teksty Drugie”, 4/5/6, s. 147–166. Cywiński Bohdan (1971), Rodowody niepokornych, Warszawa: Biblioteka „Więzi”. Czachowski Kazimierz (1934), Obraz współczesnej literatury polskiej 1884–1933, t. 1. Naturalizm i neoromantyzm, Lwów: PaństwoweWydawnictwo Książek Szkolnych we Lwowie. Czachowski Kazimierz (1938), Wacław Sieroszewski. Życie i twórczość, Lwów: Państwowe Wydawnictwo Książek Szkolnych we Lwowie. Czaplicka Maria (2013), Mój rok na Syberii, red. naukowa i wprowadzenie G. Kubica, przeł. H. Kossak-Nowocień, Toruń: Muzeum im. Marii Znamierowskiej-Prüfferowej. Giller Agaton (1867), Opisanie zabajkalskiej krainy w Syberyi, Lipsk: F.A. Brockhaus. Glebov Sergey (2014), Siberian Ruptures. Dilemmas of Ethnography in Imperial Situation, w: An Empire of Others: Creating Ethnographic Knowledge in Imperial Russia and the USSR, red. R. Cvetkovski Roland, A. Hofmeister, Budapest – New York: Central European University Press, s. 281–310. Hirsch Francine ...